A remotely-controlled micro airship for wireless coverage - Kafafy, Raed; Okasha, Mohamed; Alblooshi, Shamma; Almansoori, Hessa; Alkaabi, Salma; Alshamsi, Salma; Alkaabi, Turfa (Applied Research and Smart Technology (ARSTech), 2022)
This paper describes the design process and prototype development of a remotely controlled airship for wireless coverage. The airship is designed to be used as a platform to provide wireless coverage for rural areas. The design process follows a systematic design process for lighter-than-air vehicles, modified to impart slight heaviness to the vehicle. A remotely-controlled, thrust-vectored electric propulsion system offsets the slight vehicle heaviness. The electric propulsion system comprises two tilting rotors for takeoff, cruise, hovering, and horizontal manoeuvring. A rudder-less, rotor-less, cruciform fin design was implemented. A reduced-scale prototype of the airship was developed to prove the design concept. The airship prototype was successfully tested in an indoor environment. It was discovered that propeller tilting enables the dynamic thrust vectoring demanded by the various flight manoeuvres. If the airship can fly, no one will have to handle its flight when it is needed for wireless coverage.